2012
DOI: 10.1103/physrevb.85.195461
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of small magnetic clusters in fullerene cages: A density functional theory investigation within van der Waals corrections

Abstract: The encapsulation of magnetic transition-metal (TM) clusters inside carbon cages (fullerenes, nanotubes) has been of great interest due to the wide range of applications, which spread from medical sensors in magnetic resonance imaging to photonic crystals. Several theoretical studies have been reported; however, our atomistic understanding of the physical properties of encapsulated magnetic TM 3d clusters is far from satisfactory. In this work, we will report general trends, derived from density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Nevertheless, as we can see now, I lost evidences about quantum magnetism. It should be mentioned that Ni-atom clusters (n = 2 -6) demonstrated the similar stair magnetic trend in a gas phase and in fullerene cages (m = 60, 70, 80, 90), however, authors did not emphasize this interesting fact [2].…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Nevertheless, as we can see now, I lost evidences about quantum magnetism. It should be mentioned that Ni-atom clusters (n = 2 -6) demonstrated the similar stair magnetic trend in a gas phase and in fullerene cages (m = 60, 70, 80, 90), however, authors did not emphasize this interesting fact [2].…”
Section: Resultsmentioning
confidence: 84%
“…JMP equator, demonstrated "atypical" high magnetic activity similar to C-3 and C-4 compounds with reduced three and four Co-C bonds, respectively. It should be pointed out that the rough "Dragon's Teeth" appeared in calculations of spin magnetic moments of covered metal clusters via both VASP [2,7] and OpenMX [8,9] software, as well as LDA + U [10], GGA-PW91 [7], or GGA-PBE [2,7-9] functionals. Vienna ab initio Simulation Package (VASP) using the projector augmented wave (PAW) method is one of the most accurate packages, which is also considered as a state of the art in DFT codes [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Among the 3d, 4d, and 5d TM clusters, rhodium clusters (Rh n ) have attracted great interest due to the wide range of applications in catalysis. 6,9 Furthermore, experimental studies reported unexpected large magnetic moments for Rh n (n = 9-34), 10 which is in contrast with the nonmagnetic crystalline phase of bulk Rh.…”
Section: Introductionmentioning
confidence: 99%